Syntax of the Verbal Predicate in the Expressions like ‘Pierwszy i Drugi Zawodnik’ - Zbróg, Piotr (Respectus Philologicus, 2015)
In the Polish language there are expressions like pierwszy i drugi, taki lub inny which consist of adjectives, numerals or pronouns constituting determiners of nouns (e.g. ten czy ów zawodnik). Some of these sequences are distributional equivalents of the compound subject owing to the reference and syntax. Such a sequence, like series subject, relates to at least two referents in the extralinguistic reality and allows the occurrence of ad formam and/or ad sensum adjustment of verbs, for example: Pierwszy i drugi zawodnik mają / ma dobry czas. The habit of adjusting the person form in the Polish language is often unstable.The article discusses chosen issues concerning features of structure and syntax requirements among the sequences which function in sentences similarly to nominal series in the function of a subject.Models of syntax adjustment of verb in various types of sequences in the modern Polish were created on the basis of quantitative and qualitative analyses. Such a formulation of the rule may be directly provided in the correctness publications which codify the modern linguistic norm.
Keywords: verb syntax; compound subject equivalent